Fatigue and wear performance of bioepoxy vacuum-infused and autoclave-cured E-glass fiber reinforced polymer composite gears in mesh with a steel pinion - Bor Mojškerc; Zoran Bergant; Roman Šturm; Nikola Vukašinović (Polymer Testing, 2024)
Polymer composite gears are under investigation as a promising solution to mitigate the performance gap between polymer and metal gears. The study presented in this paper evaluates the fatigue and wear performance of E-glass fiber reinforced polymer composite gears. The E-glass fibers are vacuum infused with bioepoxy, followed by autoclave curing. High-speed milling is utilized to fabricate the gears, which are then subjected to testing at torques ranging from 0.5 to 0.8 Nm. Gear failure modes predominantly include wear combined with tooth edge intra-bundle fiber delamination due to fatigue, followed by extensive inter-ply delamination just prior to failure. Gear tooth wear volume demonstrates a nearly linear correlation with the number of cycles, with accelerated wear rates observed at higher torques. E-glass fiber polymer composite gears exhibit a shorter service life and a higher wear coefficient compared to our previously developed carbon fiber reinforced polymer composite gears. However, their performance remains fair, with a service life between that of PA6 GF30 and PA66 GF30 glass fiber reinforced gears.